Северный идентитет как основа развития традиций в исследовании арктики 1890-1917(Northern identity in Russian and Norwegian cultures as a background for polar explorations 1890-1917) - Xorkina, S. A. (Poljarnyj vestnik, 1998)
Compared to other European nations, Norwegians and Russians had an attachment to the Arctic from early on in their history. They were the pioneers in polar seafaring, and the exploration and settlement of the northern regions. For both nations, northernness became an important part of national identity. Northern identity and attachment to the Arctic created the cultural background for both Russian and Norwegian traditions of polar ex- ploration. However, if Norwegian culture confined itself to northernness, the northern identity of the Russians was only one part of a heterogeneous national identity. During the second part of the nineteenth and the beginning of the twentieth centuries the central place of northernness in Norwegian culture and national self-consciousness made polar exploration a natural part of nation-building and promoted Norwegian involvement in the Arctic. For Russia, on the other hand, this period was marked by both decline and reanimation of northern identity. It seems to be that in case of Russia, the geographic factor of the northern identity and political and economic interests in the north were of more importance than cultural predispositions for renewed research activity in the Arctic during the period 1890-1917. At the same time, cultural attributes related to the North were an important part of the Norwegian exploring tradition.